Haar Wavelet Collocation Method For Solving Stagnation Point Flow Over A Nonlinearly Stretching/shrinking Sheet In A Carbon Nanotube With Slip Effect - Hasanah N. S.; Rasedee A. F. N.; Bachok N.; Wong T. J; Hasan M. (Lviv Polytechnic National University, Academic Jou, 2024)
Indexed by Scopus